Mechanochemistry of supramolecules - Bose, Anima; Mal, Prasenjit (Beilstein Journal of Organic Chemistry, 2019)
The urge to use alternative energy sources has gained significant attention in the eye of chemists in recent years. Solution-based traditional syntheses are extremely useful, although they are often associated with certain disadvantages like generation of waste as by-products, use of large quantities of solvents which causes environmental hazard, etc. Contrastingly, achieving syntheses through mechanochemical methods are generally time-saving, environmentally friendly and more economical. This review is written to shed some light on supramolecular chemistry and the synthesis of various supramolecules through mechanochemistry.
Keywords: ball milling; mechanochemistry; self-assembly; solvent-free; supramolecular